DEVELOPING AN EXTENDED FLIPPED CLASSROOM FOR TEACHING ENGLISH AT PRIMARY SCHOOL: THE PLAN, FLIP, ASSESS, REFLECT (PFAR) MODEL - Adin Fauzi; Miza Rahmatika Aini (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
It is widely known that teacher-centered learning still dominates the current teaching and learning practice. This practice leads to an ineffective learning process since the students are not optimally engaged in it. Additionally, the teachers’ challenge is growing due to the implementation of online learning during the Covid-19 pandemic.To address these challenges, this study developed a flipped classroom named the Plan, Flip, Assess, and Reflect (PFAR) model for teaching English at primary school. This model is able to transform the traditional learning into an interactive learning process by mixturing online and face-to-face learning. The PFAR model consists of four steps: 1) planning the lesson; 2) flipping the lesson; 3) assessing learning; and 4) reflecting upon learning. The steps in developing this model include 1) need analysis; 2) design and development; 3) validation and revision; 4) preliminary field test; 5) product revision; 6) main field test; and 7) final revision and dissemination. These processes lead to a production of the PFAR model. The result of validation revealed that the quality of the PFAR model was between good and excellent. They agreed that the PFAR model is beneficial for English teachers at primary school.The result of experiment also indicated that the PFAR model had a significant effect on the students’ English speaking skill. It significantly improved the students’ speaking skill. English teachers of primary school can directly adopt or adapt the PFAR model to create an effective and interactive learning process after the Covid-19 pandemic.